Chrześcijańska bazylika rzymska – kontynuacja czy innowacja? - Kalinowski, Zygmunt (Vox Patrum, 2015)
The article is an attempt to arouse a discussion about the originality of the design of Roman Christian basilica. The author deals with the form of basilica Constantiniana and strives to reconstruct its architectonic and functional programme. Formal borrowings from forum basilicas and imperial audience halls have been indicated. The formal adoption from those objects has been justified in two ways. The idea of acquiring the scale and inside arrangement from forum basilicas stemmed from the similarity of function. In turn, hierarchical order of the interior was achieved due to an apse moved to the shorter side with the entrances on the opposite one; such a compositional solution was taken from imperial basilicas. It was aimed to focus an attention of the faithful at actions which were taking place against the apse as well as at the bishop himself. The apse’s symbolic significance raised the rank of a building, thus granting a bishop the emperor’s authority. The development of Roman Christian basilica – understood as such process – turned this object into original architectonic creation. It joined ingeniously the function of gathering the faithful (procedure unknown to the prior Roman cult architecture) with the visualisation of the symbolism of power – of a bishop, in this case – emanating from the form of the apse and from the structure of the building, both derived from imperial basilicas.